TEACHING VOCABULARY BY USING PICTURE FOR AUTISM STUDENTS - Neviyanti, Evi; Arifin, Zainal; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak : Mengajar kosata dengan menggunakan gambar untuk siswa autism. Penelitian ini bertujuan untuk menginvestigasi apakah mengajar kosakata dengan menggunakan gambar efektif atau tidak dan untuk melihat perbedaan ketercapain siswa yang mendapatkan perlakuan dengan siswa yang tidak mendapatkan perlakuan. Metode penelitian yang digunakan adalah metode eksperimen semu. Berdasarkan hasil analisis data, nilai rata-rata pre-tes kelompok eksperimen adalah 59.17 dan nilai rata-rata pos-tes nya adalah 77.50. Sedangkan nilai rata-rata pre-tes kelompok control adalah 60.00 dan nilai rata-rata pos-tes nya adalah 65.90. Didapatkan nilai t-tes adalah 6.85 dan nilai tersebut lebih tinggi dari nilai t-tabel 1.714 dengan tingkat penyimpangan 23 pada level 0.05 atau 5%. Hal itu berarti effect size adalah 2.60 dan dikategorikan efek yang kuat dan alternative hipotesis diterima. Kata kunci : kosa kata, gambar, siswa autisme Abstract : Teaching vocabulary by using picture for autism students. The purpose of this research are to investigate whether the use of picture is effective or not for teaching vocabulary, and to investigate whether the differences between the students of experimental group and students achievement of control group is significant or not of the fourth grade students with autism. The research method used in this research is quasi-experimental. Based on the result of data analysis, the mean score of experimental group in pretest was 59.17 and in posttest was 77.50. Meanwhile, the mean score of control group in pretest was 60.00 and in posttest was 65.90. The interval score between pre-test and post-test is 18.33. The the writer found the t value, which 6.85 is higher than t table 1.714 with the degree of freedom 23 at the level 0.05 or 5%. It means that the significant score of the effect size was 2.60 and categorized as strong effect and the alternative hypothesis (Ha) was accepted. Keywords : vocabulary, picture, autism students